Surgical Procedure And Future Treatment Options For Posttraumatic Syringomyelia : A Systematic Review - Ananda, Sigit; Iskandar; Hamzah, Zaini (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2022)
Objectives To find the most effective surgical procedure for posttraumatic syringomyelia (PTS) in the last 1 decade. And to look for the latest therapeutic strategies that have the opportunity to be developed in the future. Background Syringomyelia related trauma is uncommon case compared to other etiology such as Chiari Malformation type 1. The management of PTS is remain unclear and debatable. The aim of this study is to review PTS regarding surgical procedure, outcomes, and potential future treatment strategies. Methods This study uses a structured analyses focused on preferred reporting items for systematic review and meta-analyzes (PRISMA). Document selection using the keywords â€œPostraumatic Syringomyeliaâ€ AND â€œSyringomyeliaâ€ and based on publication (10 years). We selected based on the 2020 PRISMA checklist and based on inclusion and exclusion criteria. A total 17 studies met the eligibility criteria. We recorded treatment strategies, level of syrinx, severity of injury, injury to symptom duration and outcomes. Results A total 264 participants with PTS from 15 observational studies and 2 clinical trials were reviewed. We recorded 68% of participants were treated surgically (n=181). The most common procedure is arachnoid lysis and duraplasty (32,5%, n= 59) followed by syrinx shunting (15,4%, n=28) and subarachnoid-subarachnoid bypass (11%, n=20). We found that the syrinx shunting was the most successful procedure with symptoms improved in 82% of patients postoperatively. Overall, symptoms improved in 60% participants who underwent surgery (n=110). We also found deterioration from surgical procedure in 18% participants (n=32). Beside of surgical strategy we also found another therapeutic option that use mesenchymal stromal cells (MSCs) that injected into the syrinx. We recorded a 100% success rate from this procedure (n=7) Conclusion Although the overall outcomes of the surgical procedure for PTS are still unsatisfactory, the syrinx shunting procedure seems to be considered as the most effective surgical procedure. Other therapeutic strategies such as MSCs is considered promising but still require further researches with larger sample sizes. Keywords : syringomyelia, syrinx shunting, trauma